Increasing nutrient use efficiency in West-African agriculture: The impact of micro-topography on nutrient leaching from cattle and sheep manure - Brouwer, J.; Powell, J.M. (Elsevier, 1998)
In African agriculture, availability of nutrients for crop production can be increased using external inputs such as mineral fertiliser. However, for many African farmers the large scale use of external inputs will remain beyond reach for the foreseeable future. There is, therefore, also a need for increasing the efficiency of use of locally available nutrients such as manure and crop residues. Data from our manure application experiment for a pearl millet crop in South West Niger showed that, within twelve months of application of cattle manure at rates similar to those found in farmers' fields (9-10 t ha-1), on average 1070 kg ha-1 of C, 91 kg ha-1 of N and 19 kg ha-1 of P were leached to between 1.5 and 2.0 m depth (n=4). In this paper a further analysis is presented of data from that experiment, from individual plots with a range of manure application rates. All other things being equal, the lowest and wettest plots, on concave slopes, suffered the greatest leaching losses of both cattle and sheep manure and urine. The driest plots on convex slopes had the smallest losses. To obtain good millet yields, larger amounts of cattle manure and urine were needed on concave plots than on convex plotes. Sheep manure and urine appeared to be a much more efficient organic fertiliser for concave, acid, leached depressions than cattle manure. This is probably due to the fact that sheep urine increased soil pH much more than cattle urine. Given these results, there appear to be possibilities for increasing manure use efficiency in the Sahel, and elsewhere in Africa, by applying manure at different rates on different parts of a farmer's field, in accordance with micro-topographical changes. Fertiliser use efficiency could likely be increased in a similar manner.